Transgenerational inheritance or resetting of stress-induced epigenetic modifications: two sides of the same coin - Tricker, Penny J. (Frontiers in Plant Science, 2015)
The transgenerational inheritance of stress-induced epigenetic modifications is still controversial. Despite several examples of defence ‘priming’ and induced genetic rearrangements, the involvement and persistence of transgenerational epigenetic modifications is not known to be general. Here I argue that non-transmission of epigenetic marks through meiosis may be regarded as an epigenetic modification in itself, and that we should understand the implications for plant evolution in the context of both selection for and selection against transgenerational epigenetic memory. Recent data suggest that both epigenetic inheritance and resetting are mechanistically directed and targeted. Stress-induced epigenetic modifications may buffer against DNA sequence-based evolution to maintain plasticity, or may form part of plasticity’s adaptive potential. To date we have tended to concentrate on the question of whether and for how long epigenetic memory persists. I argue that we should now re-direct our question to investigate the differences between where it persists and where it does not, to understand the higher order evolutionary methods in play and their contribution.